2000
DOI: 10.1097/00005768-200002000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the menstrual cycle phase and menstrual symptoms on maximal anaerobic performance

Abstract: Although there were no significant differences in maximal anaerobic performance during different menstrual cycle phases, results of this study suggest that the presence or absence of premenstrual or menstrual syndrome symptoms may have an effect, possibly through an action on the stretch-shortening cycle of tendons and ligaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 15 publications
5
79
0
5
Order By: Relevance
“…The relationship between physical exercises and dysmenorrhea is not well established in the literature. In some athletes, dysmenorrhea symptoms remain with training, in others, the symptoms fade 45,46 .…”
Section: Menstrual Dysfunctionmentioning
confidence: 99%
“…The relationship between physical exercises and dysmenorrhea is not well established in the literature. In some athletes, dysmenorrhea symptoms remain with training, in others, the symptoms fade 45,46 .…”
Section: Menstrual Dysfunctionmentioning
confidence: 99%
“…Since the participants in the present study were oral contraceptive users and variations in strength were not verified, we may corroborate the speculation of the authors mentioned above. Conversely, Giacomoni et al (19) did not observe oscillations in anaerobic performance during the MC, regardless of the use of oral contraception, suggesting hence that the absence or presence of pre-menstrual symptoms or dysmenorrheal could affect performance. Such symptoms are derived from the oscillations of estrogen/progesterone during the MC.…”
Section: Resultsmentioning
confidence: 87%
“…Thus, the variations in the hormonal concentrations would provide better performance in the follicular phase. Nevertheless, the evidence does not support this statement (4,(8)(9)(10)17,19) . Reviewing the literature, it is observed that the issue of strength performance concerning the different phases of the MC still remains controverse (2,5,7) .…”
Section: Lutealmentioning
confidence: 92%
See 1 more Smart Citation
“…Outra limitação reside no fato de alguns estudos apontarem a variação no desempenho muscular em decorrência de flutuações hormonais durante o ciclo menstrual e utilização de contraceptivos orais (SARWARDE NICLOS; RUTHERFORD, 1996) ou de sintomas pré-menstruais (GIACOMONI et al, 2000;CHAVES;ARAúJO, 2002). Entretanto, no presente estudo não foi analisado o uso de contraceptivos uma vez que outros autores não indiquem alteração significativa de fatores relacionados ao uso de contraceptivos ou da fase menstrual para ganho de força, o que seria importante para a amostra deste estudo por se tratar de estudantes jovens (LOUREIRO et al, 2011).…”
Section: Discussionunclassified